Dehydration in Children in the Mountain - Causes and Practical Advice - Gostimirović, Miloš; Rajković, Jovana; Gojković Bukarica, Ljiljana (Medical Word, 2025)
Being in nature and numerous beneficial effects on health and disease prevention make hiking a physical activity recommended for all ages. However, this activity is not without absolute risk to health, considering that vast majority of mountaineering activities are organized at altitudes over 2000 m above sea level (highland), which can last for several days. In that case, risks caused by potentially inadequate psychophysical and ambient conditions (e.g. sprained joints, insect bites, frostbite/heat stroke, acute altitude sickness,...) must be considered, but also a dehydratation, especially in summertime. As a result of dehydration, serious health disorders can occur, which sometimes require immediate professional intervention. Therefore, it is recommended for every mountaineer who attend a physically and/or technically demanding mountaineering action, to know about the amount of water, its intake rate and factors that increase the need for water, as well as the general physiology and regulation of body fluids. More often, we see the youngest (even young infants) at the high-mountain activities, especially during the summer. The inclusion of children in mountaineering is affirmative, but it is also known that they are at greater risk for acute health disorders comparing to adults, including dehydration. The aim of this article is to give a general overview of the body fluids and provide useful practical tips for preventing dehydration of the youngest on the mountain, in order to fully express the psychophysical benefits of hiking, both for the child and for the parents.